Case report: Load, intensity, and performance characteristics in multiple grand tours - van Erp, T.; Hoozemans, M.; Foster, C.; de Koning, J. J. (Medicine & Science in Sports & Exercise, 2020)
Introduction: The aim of this study was to present the load, intensity, and performance characteristics of a general classification (GC) contender during multiple grand tours (GTs). This study also investigated which factors influence climbing performance. Methods: Power output (PO) data were collected from a GC contender from the Vuelta a España 2015, the Giro d`Italia 2017, the Giro d`Italia 2018, and the Tour de France 2018. Load (e.g., Training Stress Score and kJ spent) and intensity in five PO zones were quantified. One-way ANOVA was used to identify differences between the GTs. Furthermore, performance during the four GTs was quantified based on maximal mean PO (W/kg) over different durations and by the relative PO (W/kg) on the key mountains in the GTs. Stepwise multiple regression analysis was used to identify which factors influence relative PO on the key mountains. Results: No significant differences were found between load and intensity characteristics between the four GTs, with the exception that during the Giro d`Italia 2018, a significantly lower absolute time was spent in PO zone 5 (P = 0.005) compared with the other three GTs. The average relative PO on the key mountains (n = 33) was 5.9 ± 0.6 W/kg and was negatively influenced by the duration of the climb and the total elevation gain before the key mountain, whereas the gradient of the mountain had a positive effect on relative PO. Conclusions: The physiological load imposed on a GC contender did not differ between multiple GTs. Climbing performance was influenced by short-term fatigue induced by previous altitude meters in the stage and the duration and gradient of the mountain.